Effect of Bojanggunbi-tang and its primary constituent herbs on the gastrointestinal tract: a scoping review - Park, Chaehyun; Kim, Minjeong; Park, Jae-Woo; Kim, Jinsung; Bu, Youngmin; Ko, Seok-Jae (Frontiers in Pharmacology, 2025)
BackgroundBojanggunbi-tang (BGT), a herbal prescription used in traditional Korean medicine, has been used to treat various gastrointestinal (GI) diseases.MethodsStudies on BGT published until May 2024 were retrieved from the electronic databases of Medline, CENTRAL, Embase, AMED, CNKI, CiNii, Kmbase, KISS, NDSL, and OASIS using GI-related terms. All study types, regardless of the research method or language, were eligible for inclusion. Additional articles on Lonicera japonica, Atractylodes macrocephala, and Alisma canaliculatum, which are key components of BGT, were retrieved from the databases of Medline, CENTRAL, Embase, and Web of Science using GI-specific terms. The basic information, research models, administration methods, evaluation methods, and treatment outcomes of the selected studies were examined subsequently.ResultsFourteen studies, comprising nine animal studies, one cell-based study, and four human studies, were included in the final analysis. BGT was found to exhibit anti-inflammatory effects, promote restoration of the gastrointestinal mucosa, and regulate GI motility. Analysis of the key herbal components L. japonica, A. macrocephala, and A. canaliculatum revealed that they inhibit inflammatory cytokines and oxidative substances, regulate serotonin and cholinergic pathways, and modulate intestinal microbiota.ConclusionThis scoping review confirmed the therapeutic potential and mechanisms of action of BGT and its main components, L. japonica, A. macrocephala, and A. canaliculatum, thereby indicating its ability to enhance GI health. Further studies, including randomized clinical trials, must be conducted in the future to confirm these findings.Scoping review registrationThe study was registered in OSF, an international scoping review database: https://doi.org/10.17605/OSF.IO/ATU4S.